Aplicación de la Morfometría en la identificación de especies de la Tribu Xyleborini (Coleoptera: Curculionidae: Scolytinae) - Collantes, Ruben Darío (2021)
The aim of this study was to determine whether the morphometrics, which is the study of variation and change in structure of an organism both in shape and size, allows an adequate species identification of the tribe Xyleborini, mainly the genus Xyleborus. The species chosen for this analysis were Xyleborus ferrubineus, X. volvulus, X. affinis, X. scheldi, Xylosandrus morigerus (= Xyleborus morigerus) and Sampsonius dampfi. The dependent variables were the length of body, pronotum and elytra, width of pronotum and base of elytra, and the proportions of the body length per width of the base of elytra, length per width of pronotum and length per width of elytra. The average values of 10 specimens per species for each variable were included in a multivariate analysis for the construction of a phenogram. After comparing the results obtained with the works of Wood (1982) and Rabaglia (2006), the conclusion was that morphometrics is a very useful tool for separating species of the tribe Xyleborini, but in addition to other characters not covered in this work.